Edward Lear: A Life in Pictures. Issue 2 (1st September 2019) - Graziosi, Marco
Abstract : Edward Lear has secured a prominent position in the history of literature and travel writing thanks to his nonsense books and his journals; he is considered one of the most innovative zoological illustrators of the nineteenth century and is being rediscovered as a landscape painter in watercolour and oil. This article argues that he also deserves to be remembered among the precursors of modern comic art. His picture stories, though never published in his lifetime, represent an early instance of autobiographical graphic narrative, while his limericks, never out of print since 1861, introduced a radically innovative caricatural style and a conception of the relationship between pictures and text that strongly influenced modern comic artists.